Inference to the source. - Ahmed, Sarwar (Synthese, 2025)
It has been argued that, in scientific observations, the theory of the observed source should not be involved in the observation process to avoid circular reasoning and ensure reliable inferences. However, the issue of underdetermination of the source has been largely overlooked. I argue that concerns about circularity in inferring the source stem from the hypothetico-deductive (H-D) method. The epistemic threat, if any, arises not from the theory-laden nature of observation but from the underdetermination of the source by the data, since the data could be explained by proposing incompatible sources for it. Overcoming this underdetermination is key to reliably inferring the source. I propose a bidirectional version of inference to the only explanation as a methodological framework that addresses this challenge while circumventing concerns about theory-ladenness. Nevertheless, fully justifying the viability of the background theoretical framework and its accurate description of the source requires a broader conception of evidence. To this end, I argue that integrating meta-empirical assessment into inference to the only explanation offers a promising strategy, extending the concept of evidence in a justifiable manner.